Analysis of Factors That Influence Interest in Investing in the Capital Market for the Millennial Generation Through FinTech Technology - Tuti Supatminigsih (International Journal of Education, Vocational and Social Science, 2023)
The aim of this research is to analyze the factors that influence interest in investing in the capital market for the millennial generation through FinTech technology. Interest here is more about interest in the form of awareness about investing. This research uses qualitative research, namely research that is descriptive and tends to use analysis. In this case, the researcher conducted a semi-structured interview, which was carried out more freely compared to a structured interview. In conducting interviews, researchers use the help of an interview guide to facilitate and focus the questions that will be asked. The results of this research can be used as a benchmark for analyzing the level of investment interest among millennials, providing support and convenience for the capital market area, as well as increasing the investment interest of young investors.